2019
DOI: 10.1038/s41598-019-41918-3
|View full text |Cite
|
Sign up to set email alerts
|

Integrating gene regulatory pathways into differential network analysis of gene expression data

Abstract: The advent of next-generation sequencing has introduced new opportunities in analyzing gene expression data. Research in systems biology has taken advantage of these opportunities by gleaning insights into gene regulatory networks through the analysis of gene association networks. Contrasting networks from different populations can reveal the many different roles genes fill, which can lead to new discoveries in gene function. Pathologies can also arise from aberrations in these gene-gene interactions. Exposing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 75 publications
0
48
0
Order By: Relevance
“…In psychology, network psychometrics has been proposed as an alternative representation of psychometric constructs [26]. Network science has also been employed to map brain activity [27], understand interactions between genes [28], and analyse data from health interventions [29].…”
Section: Plos Onementioning
confidence: 99%
“…In psychology, network psychometrics has been proposed as an alternative representation of psychometric constructs [26]. Network science has also been employed to map brain activity [27], understand interactions between genes [28], and analyse data from health interventions [29].…”
Section: Plos Onementioning
confidence: 99%
“…Based on network inference (Erdem et al 2016; Grimes et al 2019; Lezon et al 2006; Subramanian et al 2005), molecular interactions and signaling pathways are identified (Fig. 1b) that may be involved in the progression of early NAFLD.…”
Section: Human Organ Microphysiology Systems (Mps) Complement Animalmentioning
confidence: 99%
“…However, these studies only provided preliminary analyses to link these changes in gene expression with IDD pathogenesis. Additionally, these genes do not play an independent role in the genome, instead they work in synergy with other genes to form pathway networks based on their intricate interactions and execute biological functions [11,12]. Therefore, it is speculated that a large number of genes and their interaction with each other are involved in the pathogenesis of IDD.…”
Section: Introductionmentioning
confidence: 99%